O ensino de sistemas de equações do primeiro grau com duas incógnitas no oitavo ano do ensino fundamental através de situações-problema - Antoniassi, Kleber Rodrigo (2013)
Working with resolution of situations-problem is of great importance on Mathematics Teaching-Learning process and on Teaching-Learning process of others disciplines, once the human being is all the time challenged to resolve problems in their daily life. The results presented on this assignment contemplate the efforts made for the validation of teaching system of first degree equation with two unknowns to the students from Middle School through situations-problem. The methodology applied was the didactic engineering. The specific goals are diluted on the stages of the methodology which are described on the introduction characterizing the previous analysis. At the stage of the analysis a priori was made the diagnosis of the difficulties presented by the students and theoretical conception. During testing we have developed a didactic sequence that we consider to be appropriate to teaching system of first degree equations bringing to the students ways of resolution, an adapted method of problems resolution, the use of teaching material as graphics board and Geogebra software. The results collected by means of the development of the didactic proposed, as well as the participation of the students on the activities proposed, observed in the analysis a posteriori will be faced with the hypothesis raised on this research assignment for the effect of validation process. We have noticed even though many teachers recognize the importance of the use of situations-problem on Mathematics Teaching, the majority doesn´t do it in satisfactory way, working mainly with the problems proposed in didactics books, without regard stages proposed on the methodology of resolution problems. Through analysis from the results achieved by the students, raising the percentage of hits in solving problems about systems of first degree equation with two unknowns in activities proposed, assessments and simulated test applied by school at the end of academic year, we can conclude that the didactic sequence presented on this assignment could propitiate the learning process.